Default Risk and the Pricing of U.S. Sovereign Bonds - DITTMAR, ROBERT F.; HSU, ALEX; ROUSSELLET, GUILLAUME; SIMASEK, PETER (Journal of Finance, 2026)
ABSTRACT We examine the relative pricing of nominal Treasury bonds and Treasury inflation‐protected securities in the presence of U.S. default risk. Hedged breakeven inflation is significantly positively related to U.S. default risk, driven by correlation between shocks to default risk and both shocks to inflation swap premia and Treasury yields. To understand the mechanisms through which default risk is related to inflation swaps and sovereign yields, we estimate an affine term structure model to capture their joint dynamics. Our estimation implies that the interaction between inflation dynamics and default is the primary source of differential pricing.